Predicting Gene-Disease Associations with Knowledge Graph Embeddings over Multiple Ontologies - Nunes, Susana Catarina Plácido (2022)
Tese de mestrado, Bioinformática e Biologia Computacional, Universidade de Lisboa, Faculdade de Ciências, 2021